Prevention of caries and obesity in children with immigrant background in Norway- a study protocol for a cluster randomized controlled trial - Mariam Reda; Abhijit Sen; Manal Mustafa (BMC, 2023)
Abstract Background Immigrants are known to experience greater socioeconomic stress and poorer well-being and to suffer more from lifestyle- and diet-related disorders than native populations. There is also evidence that children of immigrant parents are at greater risk of diverse health problems than their host country cohorts. The aim of this study is to apply and evaluate the efficacy of an early life intervention program among parents/children with immigrant background to prevent childhood caries and obesity, thereby improving the children's general health, oral health, and quality of life. Methods This is a study protocol for a cluster randomized controlled intervention follow-up study. In phase I of the study, the primary care health centers in the municipality of Bergen, Norway were randomly allocated to intervention or control groups. The intervention was carried out using the motivational interviewing technique and the common risk factor approach. The intervention group received guidance on diet/oral hygiene and the control group received standard care information. Parental knowledge and children at age 3 and 5 years old will be assessed in a prospective phase II follow-up study compared to native Norwegian controls. The primary outcome will be evaluation of change on parental oral health related knowledge and attitudes. The secondary outcome will assess the impact of the intervention on children's caries -, body mass index- and oral health related quality of life. Discussion Collaboration between dental public health and primary health care personnel on the common risk approach motivational intervention offers opportunities to address key dietary behaviors that may prevent obesity and dental caries. Providing sustainable preventive measures decreases the burden of diseases and consequently reduces health inequalities, particularly among at-risk children. Trial Registration The study is registered as a clinical trial (ClinicalTrials.gov Identifier: NCT05758454: 7 March 2023). Ethical approval has already been granted by the Regional Ethical Committee (REK) (2015/ 27,639 /REK vest) and Sikt - Norwegian Agency for Shared Services in Education and Research (Reference number 778825).